Gestão de custos ambientais em entidades hospitalares da região noroeste do Rio Grande do Sul - Lucchese, Augusto Rieger (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation has as its theme the management of environmental costs, and aims to analyze the procedures used in the management of environmental costs in hospital entities in the northwest region of Rio Grande do Sul (RS). In the methodological procedures of this study is characterized by: (I) applied research; (II) Qualitative; Specification (III); supported in the methodology of multiple case study. As data collection technique, bibliographies and national and international publications were used, through semi-structured scripts applied to the institutions responsible, document analysis and interviews in situ observations. The study sample consists of four hospital organizations located in the northwest of the state. The results showed that hospitals work out actions aimed at the protection and preservation of the environment, but show information related to these actions is not yet widespread among them, not happening a specifically managing the costs of their environmental actions. Given that many of the costs associated with environmental issues will be logged along with other costs thereby hurting processed better identify how much is spent on certain environmental actions. Therefore, it is concluded that these entities are not prepared for environmental management costs.
Keywords: Meio ambiente; Custos ambientais; Entidades hospitalares; Environment; Environmental costs; The hospital authorities; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis